SOME OBSEFIVATIONS ON THE FISHERY AND BIOLOGY OF THE RIBBONFISH EUPLEUROGRAMMUS GLOSSODON (BLEEKER - Narasimham, K A (Indian Journal of Fisheries, 2011)
In the Kakinada area Eiipleiirogrammiis glossodon forms a minor seasonalfishery from June to October. The caatch composition for the period 1966-71,length-weight relationship, size at first maturity, spawning, fecundity, and food arebriefly dealt with.